2021
DOI: 10.4317/medoral.24385
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing and system biology analysis support the "two-hit" mechanism in the onset of Ameloblastoma

Abstract: Background Ameloblastoma is the most frequent odontogenic tumor. Various evidence has highlighted the role of somatic mutations, including recurrent mutation BRAF V600E, in the tumorigenesis of Ameloblastoma, but the intact genetic pathology remains unknown. Material and Methods We sequenced the whole exome of both tumor tissue and healthy bone tissue from four mandibular ameloblastoma patients. The identified somatic mutations were integrated into Weighted Gene Co-expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…In 2014, the pioneer study by the group of Heikinheimo reported for the first time recurrent activating BRAF p.V600E mutations in ameloblastomas [9]. Considering that MAPK/ERK signaling can be activated by stimulation of transmembrane receptors, including EGFR, and that overexpression of EGFR had previously been reported in ameloblastomas, when [9], [10], [51], [52], [53] e , [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [ V600E mutation in all five ameloblastic carcinoma samples evaluated and this frequency was much higher than reported by previous studies, and therefore we did not add the results to the other ones when calculating mutation frequency.…”
Section: Ameloblastomamentioning
confidence: 99%
See 2 more Smart Citations
“…In 2014, the pioneer study by the group of Heikinheimo reported for the first time recurrent activating BRAF p.V600E mutations in ameloblastomas [9]. Considering that MAPK/ERK signaling can be activated by stimulation of transmembrane receptors, including EGFR, and that overexpression of EGFR had previously been reported in ameloblastomas, when [9], [10], [51], [52], [53] e , [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [ V600E mutation in all five ameloblastic carcinoma samples evaluated and this frequency was much higher than reported by previous studies, and therefore we did not add the results to the other ones when calculating mutation frequency.…”
Section: Ameloblastomamentioning
confidence: 99%
“…Following these pieces of research, several studies have also assessed the presence of BRAF p.V600E in conventional ameloblastoma, either by molecular techniques or a combination of mutation screening and immunohistochemistry, with mutation frequencies varying from 55 to ∼90% [10,[53][54][55][56][57][58][59][60][61][62][63]. In two studies with limited sample numbers, the mutation was detected in all samples [2/2 [64] and 4/4 [65]]. The frequency of BRAF p.V600E mutation in studies that have assessed the mutation only using immunohistochemistry varied from 33 to 79% [66][67][68][69][70][71].…”
Section: Ameloblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…Two articles that performed WES reported the presence of mutations affecting KMT2D occurring in the background of BRAF mutations [13,15]. Guan et al [13], reported 2/10 ameloblastomas to harbor non-sense mutations in KMT2D, whereas Shi et al [15], identified 1/4 ameloblastomas with a frameshift deletion in the same gene. Odontogenesis-related genes have been widely associated with the etiopathogenesis of ameloblastoma.…”
Section: Gene Mutationsmentioning
confidence: 99%
“…The prevalence of BRAF V600E in ameloblastoma ranges from 46 [6] to 90% [11], with a mean value of 68%. Other somatic mutations have been reported, either in MAPK or non-MAPK pathways [6,8,10,[12][13][14][15][16]. Some of these, such as mutations in PTEN, SMARCB1, EGFR, TP53, CTNNB1, and PIK3CA [6,[8][9][10], can occur in the background of the classical BRAF V600E mutation.…”
Section: Introductionmentioning
confidence: 99%